2009
DOI: 10.1152/ajpheart.00874.2008
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE can act as a nonhypoxic regulator of HIF-1α in human microvascular endothelial cells

Abstract: 20-HETE increases the expression of VEGF in human dermal microvascular endothelial cells (ECs). Since VEGF is regulated by hypoxia inducible factor (HIF)-1, we studied whether 20-HETE also upregulates HIF-1α using the stable 20-HETE analog 20-hydroxyeicosa-5( Z),14( Z)dienoic acid (WIT003; 1–10 μM) and found that it induced a marked increase in HIF-1α protein levels. The increases in VEGF after the addition of WIT003 preceded the changes in HIF-1α, and the increases in HIF-1α were prevented by a VEGF neutraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 49 publications
4
35
0
2
Order By: Relevance
“…These findings are consistent with other reports that 20-HETE is proangiogenic (Amaral et al, 2003;Jiang et al, 2004;Chen et al, 2005Chen et al, , 2012Miyata and Roman, 2005;Guo et al, 2007Guo et al, , 2009. In this study, we further demonstrated that 20-HETE contributes to the angiogenic functions in vivo.…”
Section: -Hete Endothelial Progenitor Cells Angiogenesissupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are consistent with other reports that 20-HETE is proangiogenic (Amaral et al, 2003;Jiang et al, 2004;Chen et al, 2005Chen et al, , 2012Miyata and Roman, 2005;Guo et al, 2007Guo et al, , 2009. In this study, we further demonstrated that 20-HETE contributes to the angiogenic functions in vivo.…”
Section: -Hete Endothelial Progenitor Cells Angiogenesissupporting
confidence: 94%
“…Accumulating evidence has implicated the existence of interactions between the VEGF signaling pathway and the CYP4A-20-HETE system. 20-HETE induces the expression of HIF-1a and its downstream target VEGF in EPC and EC (Guo et al, 2007(Guo et al, , 2009(Guo et al, , 2011. Production of SDF1a and VEGF is regulated by upstream HIF-1a (Ceradini et al, 2004;De Falco et al, 2004;Hoenig et al, 2008), and 20-HETE increases the expression of both SDF-1 and VEGF (Guo et al, 2011), suggesting that 20-HETE may be upstream of VEGF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that 20-HETE stimulates production of both VEGF and hypoxia-inducible factor-1␣ (HIF-1␣), essential regulators of angiogenic responses in ECs. In addition, 20-HETE increases EC proliferation and migration, both essential steps in the angiogenic cascade (Guo et al, 2007(Guo et al, , 2009. We also have shown that 20-HETE induces neovascularization in the rat cornea (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 68%
“…20-HETE is angiogenic both in vitro and in vivo (Jiang et al, 2004;Guo et al, 2007Guo et al, , 2009) and activates VEGF and HIF-1␣ in ECs (Guo et al, 2007(Guo et al, , 2009). In the vasculature, the main source of 20-HETE is the smooth muscle layer (Gebremedhin et al, 2000), although in the lung it also is produced by ECs (Zhu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%